Maltrato en la infancia y consumo de drogas en adolescentes de preparatoria - Tamayo-Rivas, José Roberto; Gámez-Medina , Mario Enrique; Ahumada-Cortez, Jesica Guadalupe; Valdez-Montero , Carolina (Horizonte Sanitario, 2021)
Objective: To know the relationship between abuse in childhood and drug use in adolescents. Materials and methods: Descriptive, correlational, cross-sectional study; Using stratified random sampling, high school adolescents were selected. A personal data card, the child abuse questionnaire3, and the AUDIT questionnaire were applied, validated and used in the Mexican population, in previous investigations. taking into account the regulations of the general health law regarding health research20. Results: 239 adolescents from a public high school participated, the ages ranged from 15 to 19 years (M = 16.41; SD = 1.04), women predominated with 54.5%. In the variable of abuse in childhood and subscales by sex, a significant difference was found in the physical abuse subscale, showing that men (Mdn = 7.00/M = 8.11, SD = 3.08) had a higher physical abuse score compared to women. (Mdn = 7.00/M = 7.28, SD = 2.64) with a U = 5760.0, p <.032. When correlating the variables of abuse in childhood and drug use, a positive and statistically significant correlation of the number of drugs with the total AUDIT was found: sensible consumption, harmful the total score of abuse, sexual abuse, emotional neglect and neglect physical. Conclusions: Men presented more physical abuse. In the relationship between the study variables, it was found that abuse in childhood was related to the consumption of harmful alcohol and the number of drugs consumed. Keywords; child abuse; physical abuse; substance use.